Social media use of electronic commerce in digital economy development - Khoo, Wan Yi; Ong, Tze Yee; Tan, Jia Yun; Woon, Shi Huan (2022)
After the impact of the COVID—19 outbreaks, Malaysia implemented an economic lockdown to cope with the impact. As a result, businesses went through digitalization to survive. As a growing e-commerce platform, social media has significantly played an important role in digital economy. However, Malaysia’s social commerce is still in the initial stage of growing social commerce. Hence, this study is investigating the contributing factors of social commerce and digital economy. Perceived ease of use, perceived usefulness, perceived credibility, perceived information quality, and perceived social impact are the hypothesized contributing factors. Primary data collection via online questionnaires is conducted to study this topic, 400 samples are collected from adults Malaysian. SEM-PLS is used to analyzed the data collected. As a result, perceived usefulness, perceived social impact, perceived credibility is having significant relationship with the social commerce usage. On the contrary, perceived ease of use and perceived information quality are having an insignificant relationship with the actual usage of social commerce. Perceived risk and confidence level of the information on social media prompted this result.